Pengaruh Edukasi Nutrisi Pada Pasien Diabetes Mellitus Tipe 2 Terhadap Pengetahuan Dan Level Gula Darah - Setiawan, Cencen Hendra (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Dietary compliance in diabetes sufferers is a very important problem to overcome so that sufferers can control their blood sugar levels. The family has an important role in providing support to patients so that patients feel happy and confident in dealing with illness, and enthusiastic about controlling their blood sugar levels. Method: This study used a case report with a nursing process approach which was carried out over 4 meetings. At the first meeting, data collection was carried out, the second and third meetings carried out health education and checked blood sugar levels, and the fourth meeting carried out evaluation. Results: There was an increase in knowledge among patients and families after education, with an average score of 50.00 to an average score of 80.00. Likewise, the patient's blood sugar level decreased from 299 mg/dL to 202 mg/dL after education regarding nutrition and at the third meeting it was 204 mg/dL. Conclusion: After education was carried out, there was an increase in knowledge in patients and families and there was a decrease in blood sugar levels in patients.